The church service on Martin Luther’s conception - Spehr, Christopher (Vox Scripturae - Revista Teológica Internacional, 2014)
The present article presents Martin Luther’s conception of service, according to its historical development and in its historical and theological background. The approach shows the steps that were taken for the formulation of the protestant service and demonstrates in which aspects it ruptures with the catholic tradition of the roman mass. The diverse layers or dimensions of Luther’s comprehension of the service are presented in detail. As for the theological emphasis, the division between service as work of God (service as the divine event of word and gift) and service as human work (service as expression of faith and expression of the Christian life), is presented. It’s followed by a highlighting Luther’s view of the service as a liturgical event. Finally, it is emphasized Luther’s view on the service as a dialogue between God and the human being.